Web Portal Analysis Of Agriculture As Vertical Center Smart Investment Information Hydroponic - Wulandari A A; Marzuki Marzuki (International Conference on Engineering and Technology Development (ICETD), 2017)
The level of fruit and vegetable consumption per capita in Indonesia amounted to only 34,55kg / year and 40,35kg / year, far below the recommendation food and Agriculture Organization (FAO). To meet the needs of vegetables in Indonesia needed improvements to agricultural crops. While the land area affect agricultural crops. Currently in Indonesia increasingly narrow land, especially in urban areas. Not a few residents of the city who have interest in farming. But with the condition of the land of the narrow and limited time availability dissuade make urban residents to grow crops. Not a few people who do not want to bother to grow crops. The solution to overcome these problems a hydroponic system is used.